Power play the Bush presidency and the Constitution - Pfiffner, James P.; ebrary, Inc. (Washington, D.C. : Brookings Institution Press, 2008)
"Analyzes the Bush presidency's efforts to expand executive power, putting them into constitutional and historical perspective. Explores the evolution of Anglo-American thinking about executive power and individual rights. Documents how the current administration has undermined the separation of powers and shows how these practices have imperiled the rule of law"--Provided by publisher.
A government of laws or men? -- The nature of executive power -- Creating individual rights and an independent legislature -- The American Constitution -- The power to imprison : habeas corpus -- The power to torture -- The power to surveil -- The power to ignore the law : signing statements -- Conclusion: Constitutionalism and the rule of law.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Bush, George W. -- 1946-; United States; Executive power -- United States -- History -- 21st century; Presidents -- United States -- History -- 21st century; United States -- Politics and government -- 2001-2009.; Electronic books